MENINGKATKAN PERCAYA DIRI SISWA MENYAMPAIKAN PENDAPAT DENGAN METODE REINFORCEMENT POSITIF MELALUI LAYANAN BIMBINGAN KELOMPOK - lisa sis mona; Wahidah Fitriani (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
When student’s confidence increases in expressing opinions, the learning process at school will become more effective. To get a positive identity, one of the things you must have is self-confidence. Self-confidence is an individual's positive attitude to develop a positive assessment of themselves or the environment/situation they face. This article is research that uses a quantitative approach. This research aims to find out how to increase students' self-confidence in learning and train that self-confidence through Group Tutoring services. Through Group Guidance services using the positive Reinforcement method is one method that can be used by Guidance and Counseling teachers in group guidance services. The results of the research show that students who are not confident in expressing opinions in the learning process are not only because the students do not know the answers to the questions, but because they do not have good self-confidence.